2019
DOI: 10.3390/app9214486
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Residual Biomasses and Its Application for the Removal of Lead Ions from Aqueous Solution

Abstract: The removal of water pollutants has been widely addressed for the conservation of the environment, and novel materials are being developed as adsorbent to address this issue. In this work, different residual biomasses were employed to prepare biosorbents applied to lead (Pb(II)) ion uptake. The choice of cassava peels (CP), banana peels (BP), yam peels (YP), and oil palm bagasse (OPB) was made due to the availability of such biomasses in the Department of Bolivar (Colombia), derived from agro-industrial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The surface of the biomaterial is irregular, and porous allowing a better heterogeneous biosorption due to the large interface ( Figure 2a); moreover, it presents small white spots which are caused by the presence of Calcium, Aluminium and Potassium in its structure ( Figure 3a). The SEM micrographs after adsorption (Figures 2b and 2c), show Pb(II) and Ni(II) agglomerations on their surface, which can be attributed to the formation of chelates in the samples [7], [28]. This fact is confirmed in the EDS analysis after metal removal, Figures 3b and 3c, which show the appearance of the characteristic high-intensity peaks for Pb and Ni at 1.7 and 0.8 keV, respectively.…”
Section: Characterization Techniquesmentioning
confidence: 54%
See 1 more Smart Citation
“…The surface of the biomaterial is irregular, and porous allowing a better heterogeneous biosorption due to the large interface ( Figure 2a); moreover, it presents small white spots which are caused by the presence of Calcium, Aluminium and Potassium in its structure ( Figure 3a). The SEM micrographs after adsorption (Figures 2b and 2c), show Pb(II) and Ni(II) agglomerations on their surface, which can be attributed to the formation of chelates in the samples [7], [28]. This fact is confirmed in the EDS analysis after metal removal, Figures 3b and 3c, which show the appearance of the characteristic high-intensity peaks for Pb and Ni at 1.7 and 0.8 keV, respectively.…”
Section: Characterization Techniquesmentioning
confidence: 54%
“…This event was due to the mechanisms that appear during the adsorption process of metals on bioadsorbents, which include ion exchange, microprecipitation, complexation and coordination, due to the presence of functional groups on the surface of the adsorbent [29], [30]. Figure 3a revealed that carbon and oxygen contribute more to the elemental composition of the biomass, which is attributed to the organic nature of the lignocellulosic residues [27], and its ability to capture cations by electrostatic forces [28], [31]. The presence of both heavy metals on the adsorption surface was evidenced with a mass percentage of 0.26 and 0.11%, respectively.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…N 2 adsorption/desorption isotherms of the as-prepared ZnO materials exhibited a typical type IV pattern for ZnOsf, ZnOw, ZnOr, ZnOf, indicative of mesoporous characteristics 59 and typical type III pattern for ZnOu indicating a microporous material. 59,60 The BET surface areas of various ZnO types were in the following order: ZnOsf (13.45 m 2 g À1 ) > ZnOw (10.46 m 2 g À1 ) > ZnOr (3.44 m 2 g À1 ) > ZnOf (1.59 m 2 g À1 ) > ZnOu (0.93 m 2 g À1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the spectrum, the C=O and C-O stretching in the bands around 1600 cm −1 is observed, which indicates the vibration of the carboxyl groups belonging to pectin, hemicellulose and lignin in corn cob and reported in the previous characterization of the material . The vibration of the OH groups and secondary amines between 3200 and 3600 cm −1 corresponding to the hydroxyl of the ligno-cellulosic molecules (Tejada-tovar et al, 2019). The peak observed around 2900 cm −1 can be attributed to the C-H vibrations of methyl, methylene and methoxy groups.…”
Section: Characterization Of the Bio-adsorbentmentioning
confidence: 94%